Clay new opportunities for tissue regeneration and biomaterial design - Dawson, Jonathan I (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.